Experimental study and energy analysis on microwave-assisted lignite drying. Issue 8 (11th June 2019) - Li, Longzhi; Jiang, Xiaowei; Qin, Xiaomin; Yan, Keshuo; Chen, Jian; Feng, Tai; Wang, Fumao; Song, Zhanlong; Zhao, Xiqiang
Abstract: For value-added utilization of high-humidity lignite, an investigation on its drying behavior was carried out, using a method of Microwave Thermogravimetric Analysis (MTGA). The characteristic of heat and mass transfer during drying process was studied. The effects of initial lignite mass on its drying process and energy consumption were also addressed. In addition, changes of lignite pore structure, sulfur content, and calorific value were tested after drying experiment. The results indicated that lignite microwave drying was divided into three stages: incubation stage, high-efficient dehydration stage, and deep dehydration stage. It was in agreement with the variation of temperature inside the sample. High-efficient dehydration stage and deep dehydration stage were separated at a critical moisture content. Microwave power and initial mass could be properly matched, which was effective to increase dehydration rate and decrease energy consumption. It was further noted that the best power for achieving the least energy consumption was in advance to that for achieving the greatest dehydration rate, especially for initial mass of 20 g and 25 g. The optimum power for initial mass of 20 g and 25 g was found to be 385 W and 539 W, respectively. Pore structure of dried lignite was basically deteriorated. Meanwhile, lignite microwave drying at 231 W for 6 min could lead to an increase of calorific value by 8.1% and a decrease of sulfur content by 68.6%.